Chemical Characterization, Free Radical Scavenging, and Cellular Antioxidant and Anti-Inflammatory Properties of a Stilbenoid-Rich Root Extract of Vitis vinifera. (14th December 2015) - Esatbeyoglu, Tuba; Ewald, Philipp; Yasui, Yoshiaki; Yokokawa, Haruka; Wagner, Anika E.; Matsugo, Seiichi; Winterhalter, Peter; Rimbach, Gerald
Abstract : Dietary stilbenoids are receiving increasing attention due to their potential health benefits. However, most studies concerning the bioactivity of stilbenoids were conducted with pure compounds, for example, resveratrol. The aim of this study was to characterize a complex root extract of Vitis vinifera in terms of its free radical scavenging and cellular antioxidant and anti-inflammatory properties. HPLC-ESI-MS/MS analyses of the root extract of Vitis vinifera identified seven stilbenoids including two monomeric (resveratrol and piceatannol), two dimeric (trans-ɛ-viniferin and ampelopsin A), one trimeric (miyabenol C), and two tetrameric (r-2-viniferin = vitisin A and r-viniferin = vitisin B) compounds which may mediate its biological activity. Electron spin resonance and spin trapping experiments indicate that the root extract scavenged 2, 2-diphenyl-1-picrylhydrazyl, hydroxyl, galvinoxyl, and superoxide free radicals. On a cellular level it was observed that the root extract of Vitis vinifera protects against hydrogen peroxide-induced DNA damage and induces Nrf2 and its target genes heme oxygenase-1 and γ -glutamylcysteine synthetase. Furthermore, the root extract could induce the antiatherogenic hepatic enzyme paraoxonase 1 and downregulate proinflammatory gene expression (interleukin 1 β, inducible nitric oxide synthase) in macrophages. Collectively our data suggest that the root extract of Vitis vinifera exhibits free radical scavenging as well as cellular antioxidant and anti-inflammatory properties.